APLICACIÓN DE LA PROGRAMACIÓN LÓGICA EN LA IDENTIFICACIÓN - Vilchez Chumacero, Ricardo (2019)
The present work proposes a combination of the semantic nets and the logical programming in the identification of Peruvian marine fish. Of the semantic net of marine fish, you complete the sections of Lampreys and Chimeras, for their code in SWI-Prolog (version 5.02), being created a base of knowledge of species fish marine Peruvians.